Microbial biogeography along a 2578 km transect on the East Antarctic Plateau - Victor Parro; María Ángeles Lezcano; Mercedes Moreno-Paz; Alfonso F. Davila; Armando Azua-Bustos; Miriam García-Villadangos; Jacek Wierzchos; Miguel Ángel Fernández-Martínez; Ramón Larramendi; Hilo Moreno; Ignacio Oficialdegui; Manuel Olivera; et al. (Nature Communications)
Abstract Microorganisms are present in snow/ice of the Antarctic Plateau, but their biogeography and metabolic state under extreme local conditions are poorly understood. Here, we show the diversity and distribution of microorganisms in air (1.5 m height) and snow/ice down to 4 m depth at three distant latitudes along a 2578 km transect on the East Antarctic Plateau on board an environmentally friendly, mobile platform. Results demonstrate the widespread distribution of microorganisms in the ice down to at least 4 m depth. Data point to geochemical and bacterial geographic distribution that correlate with wind trajectory and speed, modulated by local gathering and recirculation of microorganisms through snow drifting. Reservoir effects and community selection appear to occur over time, favoring microorganisms best adapted to hypothermal and hyperarid conditions. A new cyanobacterial species (Gloeocapsopsis sp) was isolated from 3 to 4 m depth. Our findings suggest that some microorganisms could exhibit transient, basal metabolic activity when associated to high salt particles, contributing to set biodiversity patterns and biogeographic compartmentalization on Antarctic Plateau ice.